Generation of Evc2/Limbin global and conditional KO mice and its roles during mineralized tissue formation. Issue 9 (10th August 2015) - Zhang, Honghao; Takeda, Haruko; Tsuji, Takehito; Kamiya, Nobuhiro; Rajderkar, Sudha; Louie, Ke'Ale; Collier, Crystal; Scott, Greg; Ray, Manas; Mochida, Yoshiyuki; Kaartinen, Vesa; Kunieda, Tetsuo; et al.
Summary Ellis‐van Creveld (EvC) syndrome (OMIM 225500) is an autosomal recessive disease characterized with chondrodysplastic dwarfism in association with abnormalities in oral cavity. Ciliary proteins EVC and EVC2 have been identified as causative genes and they play an important role on Hedgehog signal transduction. We have also identified a causative gene LIMBIN for bovine chondrodysplastic dwarfism (bcd) that is later identified as the bovine ortholog of EVC2. Here, we report generation of conventional and conditional mutant Evc2/Limbin alleles that mimics mutations found in EvC patients and bcd cattle. Resulted homozygous mice showed no ciliary localization of EVC2 and EVC and displayed reduced Hedgehog signaling activity in association with skeletal and oral defects similar to the EvC patients. Cartilage‐specific disruption of Evc2/Limbin resulted in similar but milder skeletal defects, whereas osteoblast‐specific disruption did not cause overt changes in skeletal system. Neural crest‐specific disruption of Evc2/Limbin resulted in defective incisor growth similar to that seen in conventional knockouts; however, differentiation of amelobolasts was relatively normal in the conditional knockouts. These results showcased functions of EVC2/LIMBIN during formation of mineralized tissues. Availability of the conditional allele for this gene should facilitate further detailed analyses of the role of EVC2/LIMBIN in pathogenesis of EvC syndrome. genesis 53:612–626, 2015. © 2015 Wiley Periodicals, Inc.